Fighting and negotiating with armed groups the difficulty of securing strategic outcomes - Puri, Samir 1981- (Adelphi, 2016)
"Fighting armed groups is an uncertain business, and so is negotiating. Doing both alternately, concurrently or selectively, is highly demanding. This book developes a framework to help analysts and policymakers understand the challenges of using a combination of coercion and diplomacy in dealing with armed groups. it considers which complexities have proved most inhibiting, and which have been worked around. What are the obvious traps that states fall into? What appear to be the smarter moves? Thinking in terms of 'military' or 'political solutions' is unhelpful- a strategic approach requires a fusion of coercion and negotiation. Drawing on dent disparate cases, this Adelphi book draws clear lessons for the creation and execution of a coherent stragegy for states involved in such conflicts, which often run for generations." -- From back cover